Searching for new thermoelectric materials: some examples among oxides, sulfides and selenides. (7th December 2015) - Hébert, S; Berthebaud, D; Daou, R; Bréard, Y; Pelloquin, D; Guilmeau, E; Gascoin, F; Lebedev, O; Maignan, A
Abstract: Different families of thermoelectric materials have been investigated since the discovery of thermoelectric effects in the mid-19th century, materials mostly belonging to the family of degenerate semi-conductors. In the last 20 years, new thermoelectric materials have been investigated following different theoretical proposals, showing that nanostructuration, electronic correlations and complex crystallographic structures (low dimensional structures, large number of atoms per lattice, presence of 'rattlers'…) could enhance the thermoelectric properties by enhancing the Seebeck coefficient and/or reducing the thermal conductivity. In this review, the different strategies used to optimize the thermoelectric properties of oxides and chalcogenides will be presented, starting with a review on thermoelectric oxides. The thermoelectric properties of sulfides and selenides will then be discussed, focusing on layered materials and low dimensional structures (TiS2 and pseudo-hollandites). Some sulfides with promising ZT values will also be presented (tetrahedrites and chalcopyrites).